Chemical, physical and microbial properties of casing materials used in the commercial production of white button mushrooms [Agaricus bisporus (Lange)] - Korsten, Lise (University of Pretoria, 2013)
Dissertation (MSc (Agric) Plant Pathology))--University of Pretoria, 2010.